El lenguaje de los derechos humanos como un “mal menor” (Anotaciones complementarias sobre la “practicidad”, extra-científica, de los discursos con que se reclaman esos derechos) - P. Haba, Enrique (2023)
Becoming aware of the rhetorical and interpretative- optional character that, to a great extent, those topoi gathered under the heterogeneous category of “ human rights” have, does not translate into the naiveté of thinking that this can be fixed signi ficantly. The proper (“grammatical”) logic of such discourses, their specific linguistic “region,” is not compatible with the possibility of adjusting them substantially in order to meet authentic scientif ic standards. Having said that, some human rights discourses can be useful in practice , insofar as they manage to bo lster some political and legal solutions that are especially desirable. These discour ses can help restrain abuses of power, and even participate in realizing other valuable human goals, if the material and ideological conditions of a given society allow it. However, taking into acc ount the popular support required for such purposes, in order to attract people there is always a need for forms of persuasion that respond to mythical- ideological constructions about the nature of human relationships. Among those constructions of the collective imagination, it is fair to recognize that hum an rights language, even in that form in which it is found today, currently offers the “lesser evil” with the aim of furthering, in many respects, such solutions.